Analisis Bentuk Atap Limas pada Gedung Bank Indonesia Menggunakan Pendekatan Semiotika Roland Barthes - Satria, Haris; Rahman, Muhammad Adib; Ferdiansyah, Rio; Rahali, Muhammad Alfajri (LPPM Institut Pendidikan Nusantara Global, 2025)
The Memorabilia Building “De Javasche Bank” of Bank Indonesia in Padang currently functions as a historical architectural museum, which formerly served as the economic center of West Sumatra. This study aims to analyze the historical architectural elements of the building, particularly the pyramidal roof form, through Roland Barthes’ visual semiotics analysis. Using a descriptive qualitative method, the research explores the denotative and connotative meanings of the roof as a visual sign representing the relationship between colonialism, local culture, and modernity. The findings reveal that the pyramidal roof not only serves as structural protection but also carries symbolic meanings that reflect architectural adaptation to the tropical climate and the representation of colonial power. The transformation of the building’s function into a museum signifies a shift in meaning, from a symbol of colonial economic dominance to a medium for cultural and historical preservation. These findings imply the importance of museum interpretation strategies that present visual narratives contextually and educationally, enhancing public awareness of colonial architectural values. Moreover, the results can serve as a reference for developing preservation policies based on the symbolic meanings embedded in architectural heritage. This study contributes to the discourse on historical architecture and deepens the understanding of visual elements as carriers of historical narratives. The results of this analysis can be used in the sustainability of cultural preservation in the city of Padang.